Analysis of the chemical or bacterial origin of iron sulfides on steel by time of flight secondary ion mass spectrometry (ToF-SIMS). (November 2016) - Seyeux, A.; Marcus, P.
Abstract: We report here on ToF-SIMS measurements of the 34 S/ 32 S isotopic ratio on three different iron sulfide compounds, a Pyrite substrate, a troilite layer prepared by thermal sulfidation of iron in H2 S gas, and an iron sulfide prepared by interaction of a steel sample with a medium containing Sulfate-Reducing Bacteria (SRB). The measurements performed on the three kinds of surfaces show that ToF-SIMS is perfectly suitable, after fine tuning of its performance, to distinguish the origin (chemical or bacterial) of the sulfide formed on Fe based substrates from the measurement of the 34 S/ 32 S intensity ratio. This opens the way to quick and clear determination of the origin of sulfide degradation in many industrial areas.